Comparative study of the effect of calcitonin hormone on some biochemical parameters in serum for two fish species Coptodon zillii, Astronotus ocellatus. - T. Al-Saray, Sarah (International Journal of Psychosocial Rehabilitation, 2020)
The role of calcitonin and its work mechanism is still under argument in fish. This study is trying to determine its role and factors affecting the mechanism of its work in two species of fish from different environments. The study investigates the effect of this hormone on parameters: calcium, urea, creatinine, alkaline phosphatase, FSH, and LH hormones. Coptodon zillii fish were brought from the local river environment and Astronotus ocellatus from ornamental fish shops and were acclimatized in the laboratory. The fish samples were divided into two groups. The first group was injected with 40 microliters of calcitonin for 15 consecutive days. Then they were injected every two days until the end of the experiment. Blood was pulled from the fish after three treatments, 15 days, 30 days, and 45 days, respectively. The results showed no significant differences in the calcium levels in serum for C. zillii treated with calcitonin. whereas the calcium levels in serum for A. ocellatus decreased significantly at a probability level of P ≤ 0.05. There was no significant difference in urea and creatinine levels in C. zillii. Whereas calcitonin reduced the urea levels in A. ocellatus gradually, creatinine was not affected in this species as well. alkaline phosphatase decreased in C. zillii with significant differences at the probability level P ≤ 0.05. However, its levels in A. ocellatus gradually increased with significant differences at the probability level P ≤ 0.05. FSH decreased in C. zillii with significant differences at the probability level P ≤ 0.05 but was not affected in A. ocellatus. LH was not affected by calcitonin in both species. It is concluded that calcitonin has a role in regulating calcium in fish blood, in addition to other functions, but its physiology varies according to the species.